Fabrication, Characterization, and in vitro Evaluation of Atenolol Loaded Microsponges for Ocular Delivery - Dhyani, Archana; Kumar, Ganesh (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim: The purpose of the study was development and evaluation of Atenolol loaded microsponge in situ gel for the management of ocular hypertension, glaucoma. Materials and Methods: The microsponges were prepared by modified oil in oil emulsion solvent diffusion method. The polymers used for fabrication of microsponges include Ethyl Cellulose and Eudtagit RL-100. Results: The results of particle reveals that the particle size varies from 7.33 to 9.76μm, percentage yield ranges from 59.98 to 81.22, entrapment efficiency (%) 58.23 to 80.56 and drug content (%) varies from 54.12 to 82.89. Further, the microsponges were loaded in in situ gel. The in situ gel was fabricated by using Poloxamer 407 and HPMC K4M polymers. The microsponges loaded in situ gel was evaluated for different parameters like pH, viscosity, gelling capacity, gelation temperature and drug release study. The pH varies from 6.83 to 7.43, viscosity ranges from 7421 to 15623 cp, gelation temperature ranges from 37.14 to38.22°C while the drug release ranges from 62.52 to 83.32%. At last, the stability study report indicated that the developed drug loaded microsponge in situ gel were physically and chemically stable over a period of three months. Sterility testing was conducted in the optimized formulations as per Indian Pharmacopoeia. The studies reveal that there was no sign of growth of microorganism. Conclusion: Atenolol loaded microsponge loaded in situ gel can effectively treat Glaucoma and improve the patient compliance.
Keywords: Microsponge; Atenolol; Ethyl Cellulose; Eudragit RL-100; in situ gel; Glaucoma